A Violent Need for Distance - Laurent Mellet (Sillages Critiques)
In both Ian McEwan’s The Children Act and The Disappearance Boy by Neil Bartlett (2014), violence is first deciphered in the body contact which calls for a necessary distance between characters but also subplots, so that both protagonists and literary works might be autonomous. Such salutary distance leads to an aesthetics of the rift without which the intimate connection remains threatened. Yet the distance from the event builds up a new rift soon to be violently invested as the ideal space for illusion and “misdirection”: should the rift be visible? how can violence be inflicted upon readers or spectators with a view to making them believe? Whether the distance be in focalisation or metafiction, the rift violently makes empathy irrelevant and establishes a new narrative rhythm that reshuffles fiction and posits narration no longer as the means but as the end of writing.